O turismo como projeto político e sua capacidade de indução ao desenvolvimento econômico: destinos indutores ou concentradores do desenvolvimento turístico regional em Minas Gerais? - Guilherme Augusto Pereira Malta (2018)
This research shines a light on how tourism, while the main topic of a political project, is articulated with economic development and, indirectly, the contribution of poverty reduction. The analytical incursion in the domain of these connections has its origins in the international context that, even under strong controversies, advocates in favor of this so-called potential of tourism. In the national stage, we have noticed its transformation onto political rhetoric as one of the strategic foundations to bring about economic development, restricted to employment and income generation. The object of this research is a governmental project that had as its main aim the encouragement of regional tourism development, about which we questioned how the inducing destinations participation in the project has implied in changes in the socialeconomic and tourism indicators of these towns, as in opposition to other non-participating touristic locations in the state of Minas Gerais. The use of both qualitative and quantitative approaches of this multifaceted topic was aimed at the elaboration of an integrated weave involving theoretical and conceptual views, secondary quantitative data analysis, econometric estimations, as well as in-depth debate of the empiric reality, carried out through in-loco research. The resulting picture tallies with the researchs aims, which have demanded approaches from several perspectives that would enable complementary and progressive dialogue among the topics mentioned. The indicators used were based on discussions about the predominant aspects of both the Brazilian policy for tourism and the theoretical body of the inducing destinations project. In both estimated models, apart from due distinctions, we have noticed improvements in the participating destinations, not only from the perspective of indicators such as income, rate of the legally employed, and housing infrastructure conditions, but also in the growth of formal jobs related to tourism in the catering and accommodation sectors. Finally, facing new perspectives of continuation of the inducing destinations proposal in Minas Gerais, we emphasize that the rhetoric of the regionalization program is not enough to promote the inducement of regional tourism development. The change in the status of deepening regional tourism inequalities eventually entails in the structuration of policies and mechanisms developed by local/regional actors, with the necessary foundations so that the benefits from tourism may be spread around and the inequalities lessened.